Circulating UV-vis spectrophotometry using curcumin reagent to measure borax in wet noodles - rusli , Raisani (International Journal on ObGyn and Health Sciences, 2022)
The amount of borax that is present in wet noodles was determined using a curcumin reagent as a color regent. This created rosocyanin complexes, which were then monitored using UV-Vis spectrophotometry with the maximum wave length set at 545.95 nm. Validation was performed on this method before it was utilized in a sample that was obtained from the Ciputat market. According to the findings, the calibration curve is linear between 6.25 and 50 g/ml, and the regression equation is y = 0.008 + 0.012x, with a correlation coefficient of 0.9994. The detection limit for this method was 3.1132 g/ml, while the qualification limit was 10.3775 g/ml. The recovery rate obtained through simulation for moist nodles was 99.767 1.114%. The findings of an analysis conducted on a sample of wet noodles sold at the Ciputat market revealed that four out of the five samples tested positive for the presence of borax at levels of 3.76112 0.0451, 108.592 0.02185, 117.9461 0.01455, and 6.275 0.0221 respectively.